A formação interprofissional em saúde e processo de produção de narrativas: construindo caminhos de aprendizagem - Oliveira, Claudia Maria de [UNIFESP] (2014)
The main research objective is describe and analyze the path taken by the students of Federal University of São Paulo - Campus Baixada Santista to produce narratives of life history in Health graduation courses. As specific goals are: identify studied population; investigate complicating and facilitator aspects found by students to produce their narratives; analyze students narrative production effects. This study was developed according to a quantitative-qualitative approach, by an application of a multiple choice questionnaire and semi-structured interviews. 146 students from the Health Work Thematic Area, on the Second Year Graduation Courses in Physical Education, Social Work, Physiotherapy, Occupational Therapy and Nutrition, in 2013 were invited to fill out a questionnaire, in order to characterize them as readers and writers. From these students, a sample of 18 was selected for monitoring their narrative process production during six months, by semi-structured interviews applications. These interviews were carried out in 3 phases, recorded in accordance with interviewees consent, and then transcribed. The categorization and analysis of data process was based on content analysis techniques. The results pointed that the main difficulties encountered in students narrative production process are in maintain narrated facts fidelity; pieces of information chronological organization; pieces of information choice to write in pairs using this textual genre. Pair narratives writing was also nominated as facilitator aspect. In addition, lack of writing rules and teacher supervision in classroom are considered facilitator aspects as well. Other results indicated that narratives production in pairs process by students from different Graduation Courses facilitates listening, raises awareness of teamwork, promotes agreements and professional and personal respect. It was observed that as impacts caused by textual genre production experience, on students life-styles, this activity contributed to improve students sensitive listening; College students recognize the importance of patient's life context as a complementary element to disease diagnosis; the conscience to offer more humanized service and a therapeutic relationship was aroused. Furthermore, the activity enabled breaking paradigms and prejudices; overcoming differences between pairs Areas and helped students to understand themselves better from history of others.